Too Good to be True? : The Expectations and Reality of Mine Development in Pajala, Sweden - Poelzer, Gregory A.; Ejdemo, Thomas (Arctic Review on Law and Politics, 2018)
In order to achieve legitimacy, reality must match expectations. Resource development projects, such as mining, often force small communities to make difficult decisions regarding which projects to support or reject based on whether their expectations regarding the development of a mine manifest in reality. To make this assessment, this study looks at the factors that contributed to the legitimacy of a mine in northern Sweden, focusing on the community of Pajala, where a new mine opened in 2012. We conducted interviews with local residents representing different interests that aimed to draw out what legitimized or delegitimized the mine. From these interviews, we determined that economic factors weighed most heavily in generating support for the mine. Subsequently, in order to determine if these economic expectations matched reality, we examined economic performance data on the municipality. We found that many of the factors identified in the interviews related to local outcomes and that these matched closely with economic changes associated with the mine. Given the largely positive perceptions of the mine, the congruence between economic expectations and reality validate this support from the community. Thus, our results provide insight into the factors that affect legitimacy at the local level. Validerad;2018;Nivå 2;2018-02-12 (rokbeg)